Pendampingan Pembuatan Laporan Keuangan Pada UMKM Berdasarkan SAK EMKM - Rista Arimby; Zaenal Wafa (Jurnal Akuntan Publik, 2023)
One of the business sectors that is now starting to be controlled by many Indonesians is micro, small and medium enterprises (MSMEs). The main factor in boosting Indonesia's economy is estimated to be the micro, small and medium enterprises sector. However, many MSMEs still struggle to use their accounting skills in their daily business activities. This happens because of a lack of understanding and knowledge about accounting, especially in terms of preparing financial statements in accordance with applicable accounting standards, especially SAK EMKM, and business actors still think that the preparation of financial statements is not needed to run their business.. In order for MSME owners to prepare financial statements at the end of each recording period, support is provided to MSMEs in the form of assistance to prepare financial statements based on SAK EMKM. This activity not only helps in making financial statements but also provides knowledge about the importance of accounting, especially those related to making financial statements for business activities. The results of this activity show that MSME owners are interested in trying to apply accounting science in their business activities.